Shadow Economy: State of the Art - Rodina, O.G.; Batula, V.F. (Економічний вісник Донбасу, 2013)
This article represents the current state of the shadow economy in the world. It also contains scientists’ researches. Offers several advanced methods to estimate the amount of the shadow economy. The article also represents modern dynamics methods for reducing the share of the shadow economy, proposed by European Commission.